A dynamic knee extension device improves flexion contracture before total knee arthroplasty: a randomized controlled trial. Issue 4 (July 2020) - Stone, Andrea H.; Turcotte, Justin J.; Fowler, M. Brook; MacDonald, James H.; Brassard, Marc F.; King, Paul J.
Abstract : Background: Postoperative flexion contracture (FC) after total knee arthroplasty (TKA) affects gait and causes pain and fatigue, which can result in poor patient outcomes and decreased satisfaction. This study evaluates a dynamic extension brace that may help improve extension and decrease the rate of postoperative FC. Methods: This study was a prospective randomized controlled trial of 101 patients with a FC of ≥10 degrees scheduled to undergo TKA. Primary outcome was change in maximal active extension during the perioperative period; secondary outcomes were patient-reported outcomes. Data were collected at enrollment, preoperative appointments, and 2-week postoperative appointments. Chi-squared, t tests and repeated measures analysis of variance (ANOVA) were used to evaluate the results between and within groups. Results: Fifty-five patients were in the control group and 46 in the experimental group. The mean FC in the experimental group was significantly worse at enrollment (14.22 degrees vs. 15.76 degrees, P =0.049), but improved by the preoperative appointment (15.76 degrees to 12.52 degrees, P <0.001), while the control group FC remained stable. The experimental group experienced a greater improvement in Knee Society Knee Scores and a smaller decline in Knee Society Function Scores compared with the control group. The experimental group experienced a significant improvement in Knee Injury and Osteoarthritis Outcome Score (KOOS) score through all time points (29.47 degrees to 35.84 degrees to 51.33 degrees, P <0.001), while the control group only had significant improvement from enrollment to postoperative appointment (35.06 degrees to 49.15 degrees, P <0.001). Conclusions: Patients with FC that used a dynamic knee extension brace preoperatively had improved extension before surgery and more rapid improvement in outcome measures when compared to patients treated with a standard program alone. Level of Evidence: Level I.